2007
DOI: 10.2353/ajpath.2007.060722
|View full text |Cite
|
Sign up to set email alerts
|

Pre-B-Cell Leukemia Transcription Factor 1 Regulates Expression of Valosin-Containing Protein, a Gene Involved in Cancer Growth

Abstract: Valosin-containing protein (VCP) is involved in a wide variety of cellular functions. Our previous studies showed that the enhanced expression of VCP in cancer cells correlated with invasion and metastasis of cancers. Here, the regulatory mechanism for VCP transcription was investigated. Luciferase reporter constructs containing serially deleted 5 -flanking region of the VCP gene were transfected into MCF7 mammary carcinoma cell line, in which VCP was abundantly expressed. The deletion and mutation at the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…The current results, demonstrating that the interaction between SIK2 and p97/VCP regulates ERAD, supports the possibility that SIK2, like p97/VCP, may serve as a key regulator in the ubiquitin-proteasome system and autophagy. Furthermore, this regulatory network may have significant implications in cancer biology as previous reports have shown that elevated p97/VCP levels correlate with metastasis of several types of cancers (55)(56)(57)(58) and that SIK2 is required for cancer cell growth (9). Collectively, these observations strengthen the notion that SIK2 is necessary for the proper functions and integrity of the ubiquitin-proteasome system and autophagy, which in turn are critical for cancer cell proliferation and survival.…”
Section: Discussionsupporting
confidence: 67%
“…The current results, demonstrating that the interaction between SIK2 and p97/VCP regulates ERAD, supports the possibility that SIK2, like p97/VCP, may serve as a key regulator in the ubiquitin-proteasome system and autophagy. Furthermore, this regulatory network may have significant implications in cancer biology as previous reports have shown that elevated p97/VCP levels correlate with metastasis of several types of cancers (55)(56)(57)(58) and that SIK2 is required for cancer cell growth (9). Collectively, these observations strengthen the notion that SIK2 is necessary for the proper functions and integrity of the ubiquitin-proteasome system and autophagy, which in turn are critical for cancer cell proliferation and survival.…”
Section: Discussionsupporting
confidence: 67%
“…While VCP has been shown to be involved in a wide variety of cellular processes, including transcriptional regulation, membrane fusion, cellcycle control and cell growth (reviewed in Wang et al, 2004), the detailed mechanisms of VCP function have yet to be fully elucidated. VCP expression has been correlated with high disease recurrence rate and poor prognosis in several cancers (Tsujimoto et al, 2004;Yamamoto et al, 2004Yamamoto et al, , 2005 and it has been shown to play an important role in invasion and metastasis of cancer cells via its activation and regulation of the NF-kB (Asai et al, 2002;Dai et al, 1998;Qiu et al, 2007;Zhang et al, 2007), a transcription factor involved in apoptosis, invasion and cell proliferation. Several recent studies have shown that VCP is a coimmunoprecipitated target of Activated serine-threonine kinase (Akt), which phosphorylates VCP (Livingstone et al, 2005;Vandermoere et al, 2006) and is required for cell survival (Klein et al, 2005;Vandermoere et al, 2006Vandermoere et al, , 2007.…”
Section: Discussionmentioning
confidence: 99%
“…As most pathogenic mutations in VCP that have been detected in IBMPFD and ALS are found in the N-terminal domain, the L1 linker and the D1/ATPase domain ( Fig. 1a), we screened ten exons [1][2][3][5][6][7]10,13,14,17] harbouring most known mutations found in ALS and IBMPFD together with 5′UTR and 3′UTR regions of the gene that have not been extensively studied before. The FALS cohort consisted of 102 index cases, from which known mutations in SOD1, VAPB, TARDBP, FUS and DAO genes had been previously excluded.…”
Section: Resultsmentioning
confidence: 99%